Fiscal Federalism and Government Size in Transition Economies : The Case of Moldova. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper examines the relationship between fiscal decentralization-the assignment of revenue sources and expenditure functions across government levels-and government size in Moldova. The empirical results-based on data for a cross-section of Moldovan subnational governments in 1998-suggest that fiscal decentralization is associated with larger subnational governments and that the country's revenue-sharing system imposes a constraint on subnational spending. Moldova is currently undergoing unprecedented reform of its system of intergovernmental fiscal relations, and consolidation of its local government. This reform package is crucial to ensure that decentralization does not increase the size of government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet